(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Understanding intraspecific phenotypic plasticity is a prerequisite to fish stock identification and sustainable fisheries management. In this study, we assessed intraspecific phenotypic plasticity in terms of meristic and morphometric characters of wild populations of elongate glassy perchlet, Chanda nama from two different rivers, namely Madhumati River – Narail (MRN) and Tulshiganga River – Jaypurhat (TRJ), and an ox-bow lake, Jhapa Baor – Jashore (JBJ) in Bangladesh. Materials and Methods: In this study, six meristics, 15 conventional morphometrics, and 23-truss-based morphometrics were subjected to a one-way analysis of variance (ANOVA), followed by the Tukey-HSD test. The mean values of three meristic counts and nine conventional and 12 truss-based morphometrics demonstrated significant differences in the ANOVA test. Furthermore, principal component analysis (PCA) and discrimination function analysis (DFA) were performed separately using conventional and truss-based morphometric data. Results: In PCA analysis, four principal components were extracted and cumulatively demonstrated 51.848%. On the contrary, two discriminant functions (DF1, 63.5%; DF2, 36.5%) resulted from DFA analysis. In the bi-plot alignment from the discriminant space, all individuals were exceedingly separated among the three inhabitants. A dendrogram developed using conventional and truss morphometric characters confirmed that two clusters were formed among three populations. The TRJ population formed a distinct cluster, and the JBJ population formed a different cluster with a subcluster of MRN. In the discriminant function analysis, precise classification outcomes displayed 82% of individuals into their unique populations, whereas 66.9% of individuals were categorized as a cross-validated assemblage. Conclusion: The baseline information resulting from the current study would be useful for environmental studies and further conservation of glassy perchlet populations in Bangladesh. J. Adv. Vet. Anim. Res., 7(4): 585-596, Dec 2020 http://doi.org/10.5455/javar.2020.g456